GHO A SAN GUNAWAN : VETERAN TIONGHOA MASA REVOLUSI NASIONAL DI JAMBI 1945-1949 - Ayu Lestari. NS, Putri (Universitas Batanghari Jambi, 2024)
This study aims to describe the background of Gho A San Gunawan's life and his role in the independence and post-independence revolutions of 1945-1949. This research uses historical research methods, the method consists of four stages, namely Source Collection (Heuristics), Source Criticism, Interpretation, and Writing (Historiography). The results of this study illustrate that the warrior figure Gho A San Gunawan who is an ethnic Chinese has an important role in defending and defending the independence of the Republic of Indonesia in 1945-1949. In 1945 Gho A San Gunawan was accepted as a TKR in Jambi and was placed in the Army in the stock section in accordance with his expertise in mechanics in charge of repairing weapons, and all related to machinery. Then in 1948 it was transferred to the Air Force (AURI) which was in charge of maintaining the Catalina RI 005 aircraft. During the revolution in Jambi, Singapore had an important role for the supply of weapons and an important role for Gho A San Gunawan as a technician and driver of guerrilla ships. Gho A San Gunawan is one of Jambi Veterans who really cares about Jambi's history.